Experimental Study on the Modification Mechanisms of Dispersive Soil Treated with Hydroxyl Aluminum. (23rd June 2022) - Liu, Jie; Chen, Pan; Lu, Zheng; Yao, Hailin
Abstract : Dispersive soil is a special clay that is easy to disintegrate and disperse into particles and suspend in water, which can easily cause erosion and piping damage of dams, grooves, and road slopes. In this study, a new dispersive clay modifier hydroxyl aluminum (a positively charged aluminum hydroxide electrolyte) was proposed. Previous studies have shown that it can well coat montmorillonite in clay and combine with it to stabilize the properties of clay. The modification effect and interaction mechanism of hydroxyl aluminum on dispersive soil were studied through indoor dispersion discrimination, physical and mechanical, and micro mechanism tests (SEM and XRD). The experimental results indicate the following: With the increase of hydroxyl aluminum content, the dispersion of dispersed soil decreases and becomes nondispersive soil. Hydroxyl aluminum has an excellent inhibiting dispersion effect on dispersive soil, and it has the "agglomeration" and "cementation" effect on the dispersive soil particles. The addition of hydroxyl aluminum makes the dispersive soil agglomerated crystals arranged closely, and the number of pores between the particles reduces clearly, making the dispersed particles agglomerated. It can also reduce the alkalinity of the clay and make the clay structure more stable to restrain the dispersion of clay.